Searching for the first bass drum pedal: Rock harmonicas to Viennese pianos - Archibald, Paul (Popular Music History, 2016)
The drum kit is an instrument of great importance to most forms of popular music ever since its conception in the late nineteenth century. The bass drum pedal is key to bringing the drum kit together; utilizing the player’s foot gives freedom for both hands to be used elsewhere. This device is considered to have been invented for the first trap drummers, and it is true that the drum kit was truly born when the bass drum pedal became adopted amongst early percussionists. However, this article presents a history of the bass drum pedal that predates the drum kit far earlier than previously considered.